Emerging role of SENP1 in tumorigenesis and cancer therapy - Lin, Min; Zhang, Man; Yi, Bei; Chen, Jinchi; Wen, Siqi; Chen, Ruiqi; Chen, Tianyu; Li, Zhao (Frontiers in Pharmacology, 2024)
Acting as a cysteine protease, small ubiquitin-like modifier (SUMO)/sentrin-specific protease1 (SENP1) involved in multiple physiological and pathological processes through processing the precursor SUMO protein into mature form and deSUMOylating target protein. It has been reported that SENP1 is highly expressed and plays a carcinogenic role in various cancers. In this paper, we mainly explore the function and mechanism of SENP1 in tumor cell proliferation, apoptosis, invasion, metastasis, stemness, angiogenesis, metabolism and drug resistance. Furthermore, the research progress of SENP1 inhibitors for cancer treatment is introduced. This study aims to provide theoretical references for cancer therapy by targeting SENP1.